Implementing Trade Logistics Reforms in Complex Multi-Country and Regional Settings : The Case of the Western Balkans - Gabrielyan, Gagik; Konar-Leacy, Violane (World Bank, Washington, DC, 2015)
Trade facilitation connects economies and provides opportunities for business growth. However, the national agencies involved in trade often have different objectives, lack coordination with peer agencies in other countries because of different national priorities, high workloads, and absence of platforms to consult with each other. Such a divergence of interests is a challenge when the goal is to address, and seek consensus on, trade issues on the regional level, while undertaking capacity building and reform activities at the country level, all with the objective to benefit the private sector. The International Finance Corporation (IFC) Western Balkans trade logistics project faced this challenge. In addition, the project was constrained by limited financial resources, so marrying effectiveness and efficiency was key to achieving results. This smart lesson summarizes lessons learned from the project implementation.